Expressive Speech Acts Used by Jude Bellingham in His Personal Brand Development on Youtube - Nuralam, Muhammad Aria Ekaputra; Suswanto, Deni; Listiani, Toneng (Journal of English Language and Education, 2025)
Language plays a vital role in expressing human emotions, intentions, and identities across various social contexts. Within the framework of speech act theory, expressive speech acts serve as a medium through which speakers convey psychological states and attitudes toward particular situations. This study examines the types and functions of expressive speech acts used by Jude Bellingham in his personal brand development through his YouTube documentary. The research applies Searle’s (1969) classification of expressive speech acts and Ronan’s (2015) typology to analyze how Bellingham communicates emotions, attitudes, and social values in authentic, context-rich settings. A qualitative descriptive method is employed, using naturally occurring linguistic data from the documentary to identify and interpret expressions of gratitude, pride, humility, and empathy within Bellingham’s discourse. The findings reveal that expressive speech acts play a crucial role in shaping his public persona, reinforcing his authenticity, maturity, and relatability as a global athlete. Furthermore, the study highlights the intersection of linguistic expression, cultural adaptation, and personal branding in the digital era. This research contributes to the field of pragmatics by expanding the analysis of expressive speech acts into the domain of sports communication and digital self-presentation.